2018
DOI: 10.1038/s41598-018-35386-4
|View full text |Cite
|
Sign up to set email alerts
|

Nezara viridula (Hemiptera: Pentatomidae) transcriptomic analysis and neuropeptidomics

Abstract: Stinkbugs (Hemiptera: Pentatomidae) are of major economic importance as pest of crops. Among the species composing the stinkbug complex, Nezara viridula is one of the most abundant in Brazil, Argentina and the Southern USA. However, this species has been poorly characterized at the genetic and physiological level. Here we sequenced and analyzed the complete transcriptome of N. viridula male and female adults. We identified neuropeptide precursor genes and G-protein coupled receptors for neuropeptides in this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 85 publications
(130 reference statements)
1
20
0
6
Order By: Relevance
“…Moreover, we observed that most of the particular paralogues and splicing variants initially detected in B. mori seem to be a characteristic of Lepidoptera rather than a possible consequence of domestication of the silkworm, as previously hypothesized (Roller et al, 2008). The results presented here suggest that the neuroendocrine system structure is highly conserved in Lepidoptera, compared, for example, to Hemiptera or Coleoptera, where gene duplications and splicing variants, among other characteristics, seem to differ in a higher degree (Lavore et al, 2018; Veenstra, 2019).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Moreover, we observed that most of the particular paralogues and splicing variants initially detected in B. mori seem to be a characteristic of Lepidoptera rather than a possible consequence of domestication of the silkworm, as previously hypothesized (Roller et al, 2008). The results presented here suggest that the neuroendocrine system structure is highly conserved in Lepidoptera, compared, for example, to Hemiptera or Coleoptera, where gene duplications and splicing variants, among other characteristics, seem to differ in a higher degree (Lavore et al, 2018; Veenstra, 2019).…”
Section: Discussionmentioning
confidence: 73%
“…This finding, together with the clustering of ILP genes in the genome (Kanost et al, 2016), reinforces the hypothesis that the big expansion in ILP family is a recent event during Lepidoptera evolution, not present in all the species from this order. Those genomes having several insulin paralogues usually possess zero or one neuroparsin (NPA) gene (Lavore et al, 2018; Veenstra, 2016). On the contrary, those species encoding several NPA genes in their genomes have a small number of ILPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, transcriptomic approaches provide the foundation for identifying gene targets associated with pheromones, pesticide resistance, and other features with potential for pest managing. Conversely, only five species of stink have had full body transcriptomes sequenced to date: the brown marmorated stink bug [10], the harlequin bug [9], the southern green stink bug [11], the brown stink bug [12], and the predatory stink bug Arma chinensis [13]. Genomic data are even more scarce, comprising four genomes assembled to date: Halyomorpha halys [14], Euschistus heros, Piezodorus guildinii, and Stiretrus anchorago.…”
Section: Contextmentioning
confidence: 99%